Reducing spoilage in intermediate moisture pet foods using food-safe additives as a model system - Deliephan, Aiswariya (Kansas State University, 2022)
Safety of foods, including pet food, is affected by the presence of pathogenic bacteria, molds, and mite infestation. Intermediate moisture foods (IMFs) with water activity (a[subscript w]) of 0.60-0.85 are susceptible to storage mite and mold contamination. Control of mites depends on chemical methods such as fumigation. Methyl bromide which was used as a fumigant for stored products is now banned in many countries because of its ozone-depleting effects. Effective alternatives to methyl bromide are needed to develop integrated pest management programs for mites. Another risk for human and animal food safety is spoilage and mycotoxin contamination due to the presence of storage molds. Synthetic mold inhibitors like potassium sorbate have been used to control mold growth in IMFs but a natural alternative is desired for ‘clean labeling’ of foods in accordance with the current consumer trend. Liquid smoke is a naturally derived flavor and preservative with known antimicrobial properties; it may have potential antimycotic and acaricidal properties. Even though IMFs are below the minimum water activity for most bacterial growth (0.90 a[subscript w]) they are susceptible to pathogenic bacteria through post processing cross-contamination. The organic acid 2-hydroxy-4-methylthio-butanoic acid (HMTBa) has been used as a methionine supplement in animal feed and potentially has antimicrobial effects. The first objective of this study was to investigate the efficacy of eight liquid smoke preparations on the survivorship and orientation behavior of the cheese or mold mite, Tyrophagus putrescentiae Schrank (Acaridae: Sarcoptiformes), in semi-moist pet food. Survival of T. putrescentiae on treated (0.3% smoke inclusion) and untreated (0% smoke) pet food samples was determined by enumerating their population at 7, 14, and 28 days post-infestation. Further, semi-moist pet food cubes were dipped in smoke preparations at 0, 0.3, 1, 5, 10, 25, 50, and 100% concentration, and used in two-choice behavioral assays. The attraction or repulsion of mites towards treatments was determined by the repellency index (RI). The second objective of this study was to determine the effects of liquid smoke on shelf-life and growth of the storage mold, Aspergillus flavus Link (Trichocomaceae: Eurotiales), in semi-moist pet food with liquid smoke inclusion at 0, 0.5, 1, 2 and 4% (w/w). Shelf-life was estimated by storing samples at 28°C and 65-70% RH over 30 days and recording the number of days for the appearance of visible wild-type mold. In another experiment, samples inoculated with A. flavus were analyzed for fungal growth at sampling intervals of 2 days over a 35-day period. The third objective of this study was to evaluate the antimicrobial and residual effects of two types of organic acid mixtures, Activate DA™ and Activate WD-MAX™, containing HMTBa against Salmonella enterica Le Minor & Popoff (Enterobacteriaceae: Enterobacterales), Escherichia coli Castellani & Chalmers (Enterobacteriaceae: Enterobacterales), and A. flavus in pet food kibbles. Activate DA at 0, 1, and 2% (w/w), and Activate WD-MAX at 0, 0.5, and 1% (w/w) were tested as coating on the kibbles inoculated with the target pathogens. The fourth and final objective of this study was to evaluate Activate DA and WD-MAX on food contact surfaces like rubber, plastic, stainless steel, and concrete against Salmonella enterica contamination. Results from the studies with liquid smoke against mites indicated that the smoke did not kill or inhibit mite population growth when compared to the untreated; however, smoke preparations with high carbonyl content may provide repellency to retard mite infestation in semi-moist pet food. The shelf-life study indicated that smoke preparations with high carbonyl, and medium to low phenol content were the most effective in prolonging the number of days to occurrence of visible mold (26-28 days) compared to the untreated (7.7 days). The mold challenge study with A. flavus indicated that smoke preparations containing high carbonyls and low phenols significantly reduced mold counts by 1, 1.7, and 2.5 logs when compared to the untreated at 1, 2, and 4% concentrations, respectively. Studies with the organic acid mixtures coating on pet food kibbles indicated that Activate DA at 2% and Activate WD-MAX at 1% decreased Salmonella counts by 4 to 4.6 logs, and E. coli counts by ~3 logs after 24 h compared to the untreated samples. Levels of A. flavus did not vary up to 7 days, and subsequently started to decline by ~3.8 logs after 28 days for Activate DA and WD-MAX at 1 and 2%, respectively. At 1%, Activate WD-MAX reduced Salmonella counts by 3.1 logs on stainless steel surfaces, which was the highest, and 0.2 logs on rubber from automobile tire which was the lowest, across treatments. On both kibbles and surfaces Activate WD-MAX was more effective at a lower concentration (1%) than Activate DA (2%). Evaluating residual effect of the organic acid mixtures indicated that across treatment levels, Activate DA and WD-MAX had similar effect in reducing Salmonella counts by 4.2-4.4 logs on day 30, and 3.4-3.6 logs on day 90, compared to 4.3-4.4 logs on day 1. Across days, there was difference in the residual efficacy of organic acid mixtures on day 90, which was lesser by 0.8 logs, compared to day 1 and day 30.
Keywords: Semi moist pet food; Liquid smoke; HMTBa; Tyrophagus putrescentiae; Aspergillus flavus; Salmonella